Advancing genetic testing for neurological disorders in Tanzania: importance, challenges, and strategies for implementation - Alimohamed, Mohamed Zahir; Siima, Angela Augustine; Manji, Mohamed (Frontiers in Neuroscience, 2024)
This manuscript discusses the critical need for advancing genetic testing capabilities for neurological disorders (NDs) in Tanzania, emphasizing the importance, challenges, and strategies for implementation. Neurological disorders, often caused by a complex interplay of genetic and environmental factors, disproportionately affect low and middle-income countries like Tanzania. Patients with neurogenetic diagnoses in Tanzania face substantial obstacles, including lack of trust in medical professionals, stigmatization, and limited access to proper care. The manuscript underscores the infancy of genetic testing implementation for NDs in Tanzania, citing challenges such as high costs, limited availability, and the absence of routine testing in diagnostic procedures. The paper recommends establishing well-characterized cohorts, conducting a nationwide emergency census survey, and enhancing diagnostic services and healthcare financing. The paper stresses on the importance of collaboration, research, public awareness, and advocacy to address the challenges posed by NDs in Tanzania. The manuscript proposes a comprehensive plan, including training and capacity building in molecular diagnosis and bioinformatics, to establish genetic testing capabilities and reduce the burden of NDs in the country. Overall, the manuscript calls for a collaborative effort involving government support, stakeholder engagement, and international partnerships to advance genetic testing and improve healthcare outcomes for individuals with neurological disorders in Tanzania.